Effects on Cutting Forces in Shaping Operation - Dhiman, Kulbir (International Journal For Research In Mechanical & Civil Engineering, 2017)
In this paper, the effect of tool rake, tool shape, tool radius and tool material on the cutting forces was investigated when machining mild steel work piece material. The machining tests were carried out on a shaper. For cutting force measurement, a test setup that was designed and constructed for cutting force measurement was used. The beam type load cells were used to construct the setup and cutting force measurement readings were recorded on a computer during the tests. The MINITAB15 software is used to draw main effect plots and interaction plots between parameters. In the measurement of the cutting forces, elastic defections of the cutting tool due to the cutting forces were measured by means of the load cells located suitable position on the cutting tool .The effect of process parameters like feed, cutting speed, depth of cut, tool material, tool shape and tool geometry is seen on the cutting forces.